(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
Ionic liquid [Emim]OH is reported an efficient catalyst for one pot multi component synthesis of Polyhydroquinolines via the Hantzsch reaction. The mild reaction conditions, short reaction times, high yields and the remarkably low toxicity of ionic liquid makes this methodology greener and efficient